2020
DOI: 10.1007/s00402-020-03697-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome after lumbar spinal fusion surgery in degenerative spondylolisthesis: a 3-year follow-up

Abstract: Introduction Lumbar spinal fusion surgery is a widely accepted surgical treatment in degenerative causes of lumbar spondylolisthesis. The benefit of reduction of anterior displacement and restoration of sagittal parameters is still controversially debated. Purpose of the underlying publication was to analyze the influence of radiographic sagittal parameters of the spine in aspects of changes in postoperative clinical outcome. Materials and methods By prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Liu et al found comparable short-term functional results in 226 patients undergoing TLIF and PLIF procedures (3). Lenz et al reported on their three-year observation of the clinical outcome after lumbar spinal fusion surgery for DLS (9). The authors confi rmed signifi cant benefi ts in patients after surgery; moreover, they showed a considerable restoration of anterior displacement and sagittal rotation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Liu et al found comparable short-term functional results in 226 patients undergoing TLIF and PLIF procedures (3). Lenz et al reported on their three-year observation of the clinical outcome after lumbar spinal fusion surgery for DLS (9). The authors confi rmed signifi cant benefi ts in patients after surgery; moreover, they showed a considerable restoration of anterior displacement and sagittal rotation.…”
Section: Discussionmentioning
confidence: 97%
“…These clinical symptoms have to correlate with radiological fi ndings on Xray and MRI. The surgical treatment aims to stabilize, reduce the displaced vertebra (return to position), decompress and remove nerve compression (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…and Boxall et al . 21 , 25 Figure 1 illustrates how the gliding angle, and the sagittal rotation were defined and measured. The grade of spondylolisthesis was defined by the Meyerding classification.…”
Section: Methodsmentioning
confidence: 99%
“…Two different orthopedic surgeons measured the spinopelvic parameters including sacral slope, sacral inclination, pelvic tilt, pelvic incidence, lumbar lordosis, gliding angle, sagittal rotation and the percentage of anterior displacement of the vertebral body as described by Lenz et al . and Boxall et al 21,25 . Figure 1 illustrates how the gliding angle, and the sagittal rotation were defined and measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation